Brand Building Strategies of SMEs in Yemen:A Grounded Research that Investigates if Yemeni SMEs Follow Western Theory in Brand Building Practices - Al-Saqqaf, Raidan Abdulaziz (2005)
Today’s discourse of globalization is highly influenced by western powers; it is no news that this is evident in all walks of life starting with the global political economy and international trade, to the media and the collective body of knowledge, resulting in a less accurate representation of the global scenario, resulting in creating a new world economy based on western conceptualization & theory. Nevertheless, the experience of multinational corporations such as Procter & gamble, McDonalds and Microsoft in their globalization processes’ have indicated time and again that one of the most important obstacles they faced during their globalization process was the issue of culture, as the discourse of globalization is motivated by harvesting international business opportunities, rather than by cultural bridging.